Applying of the program codes for modeling the electron accelerator driven subcritical assembly - Ayzatskiy, M.I.; Dovbnya, A.M.; Khazhmuradov, M.A.; Prokhorets, I.M.; Prokhorets, S.I.; Rudychev, Y.V. (Вопросы атомной науки и техники, 2005)
Some physical aspects of the electron accelerator driven subcritical nuclear assembly are considered. Results of
calculations of some parameters of target and homogeneous subcritical assembly are presented. Розглянуто деякі фізичні аспекти роботи підкритичної реакторної збірки, керованої пучком
прискорювача електронів. Наведено результати розрахунків окремих параметрів мішенного пристрою та
гомогенної підкритичної збірки. Рассмотрены некоторые физические аспекты работы подкритической реакторной сборки, управляемой
пучком ускорителя электронов. Приведены результаты расчета отдельных параметров мишенного
устройства и гомогенной подкритической сборки.